Media freedom with integrity and ethics - Satendra Nandan (Asia Pacific Network, 2014)
In Fiji, too much damage had been done by tendentious propaganda by a few that had frayed the fabric of the Fijian society at so many levels of social harmony and political growth of a young democratic nation. And once a nation (and a person) suffers heart-attacks, it must take care of its daily diet and exercise both restraint and responsibility. This is never more important than during an election. This commentary argues that freedom of the press, academic freedom and parliamentary privilege, are advanced and strengthened by those who practise these with professional ethics and personal integrity and conscientiously deepen public trust, individually and collectively. When the institutions are diminished, everybody is diminished.